A Review of Injectable and Implantable Biomaterials for Treatment and Repair of Soft Tissues in Wound Healing. (5th June 2017) - Chou, Shih-Feng; Gunaseelan, Simi; Kiellani, Mhd Hussam Hijazi; Thottempudi, Venkata Vamsi Krishna; Neuenschwander, Pierre; Nie, Huarong
Abstract : The two major topics concerning the development of nanomedicine are drug delivery and tissue engineering. With the advance in nanotechnology, scientists and engineers now have the ability to fabricate functional drug carriers and/or biomaterials that deliver and release drugs locally as well as promote tissue regeneration. In this short review, we address the use of nanotechnology in the fabrication of biomaterials (i.e., nanoparticles and nanofibers) and their therapeutic function in wound healing as dressing materials. Furthermore, we discuss the use of surface nanofeatures to regulate cell adhesion, migration, proliferation, and differentiation, which is a crucial step in wound healing associated with tissue regeneration. Given that nanotechnology-based biomaterials exhibit superior pharmaceutical performance as compared to the traditional medicine, this short review provides current status and future directions of how nanotechnology is and will be used in biomedical field, especially in wound healing.